Implementation Outdoor Learning Activities (OLA) to Develop Early Childhood Language Skills - Khusnul Laely; Lilis Madyawati; Hermahayu Hermahayu; Syakilla Fatkhia Rizki; Chomisah Chomisah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Aspects of language is one aspect that is owned by early childhood that must be stimulated. At this time, children's language skills have not been optimally stimulated and have not been designed through interesting activities. The aim of this research is to describe the need to implement early childhood language development through Outdoor Learning Activity. This study uses a survey method. The subjects were educators at Early Childhood Education institutions under the auspices of Himpaudi Magelang Regency, the Bustanul Athfal Teachers' Association, the Raudhatul Athfal Teachers' Association totaling 40 educators. The data collection tool used a questionnaire at the FGD event to identify the implementation of OLA in developing early childhood language. The analysis technique uses descriptive analysis, namely describing facts with the right interpretation to recognize phenomena and to describe accurately some of the phenomena, groups or individuals that are happening. The results showed that 27.03% of educators had implemented OLA every day and had not optimally developed children's language skills. Stimulation of children's language is still carried out monotonously in the classroom by using conversation method by 24%, storytelling 22%, and question and answer 11%. So that it has not fulfilled the BAN PAUD and PNF accreditation instruments, namely education units that apply interesting learning activities outdoors to get at least 30 minutes of sunlight every day. This supports the need for OLA learning designs to take advantage of the potential of the child's environment.